2022
DOI: 10.3389/fvets.2022.842074
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Heritable Prominent Double Muscle Buttock Rabbits via Novel Site Editing of Myostatin Gene Using CRISPR/Cas9 System

Abstract: Rabbits have been domesticated for meat, wool, and fur production, and have also been cherished as a companion, artistic inspiration, and an experimental model to study many human diseases. In the present study, the muscle mass negative regulator gene myostatin (MSTN) was knocked out in rabbits at two novel sites in exon3, and the function of these mutations was determined in subsequent generations. The prominent double muscle phenotype with hyperplasia or hypertrophy of muscle fiber was observed in the MSTN-K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…In chickens, the alteration of genes involved in embryonic development has led to improved hatchability [ 71 ]. The change in bone development-related genes has also led to improved skeletal health and meat quality in pigs [ 72 ]. Besides, a study on the CRISPR/Cas9 method showed that heritable double muscle buttocks in rabbits could be achieved through myostatin mutation, which was useful for producing rabbit meat [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…In chickens, the alteration of genes involved in embryonic development has led to improved hatchability [ 71 ]. The change in bone development-related genes has also led to improved skeletal health and meat quality in pigs [ 72 ]. Besides, a study on the CRISPR/Cas9 method showed that heritable double muscle buttocks in rabbits could be achieved through myostatin mutation, which was useful for producing rabbit meat [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…MSTN-null mice showed a dramatic and widespread increase in skeletal muscle mass [56]. Other studies had showed that MSTN gene has effects on skeletal muscle development in cattles [57], goats [58], pigs [59], and rabbits [60,61].…”
Section: Degs Analyzed At Four Stagesmentioning
confidence: 99%